Medieval Spain culture, conflict, and coexistence : studies in honour of Angus MacKay (Palgrave/Macmillan, 2002)
"The history and literature of Spain in the Middle Ages were marked by the extraordinary richness and diversity of the cultural components that coexisted, however uneasily, in the Iberian Peninsula in these centuries. Muslims, Christians and Jews enjoyed a variety of relationships, differing according to period and region, that ranged from mutual toleration and cultural exchanges, to wars, pogroms and ethnic cleansings. But divisions did not always run along ethnic or religious lines. Within the three religious traditions there was also much diversity, and this in turn could generate episodes of internal conflict. New cultural currents began to make themselves felt in the fifteenth century, not least from Italian humanism, which manifested themselves in a variety of literary forms. The rich and often violent interplay of cultures that made up medieval Spain from the eleventh to the early sixteenth centuries is the subject of these essays, contributed by some of the foremost American, British and Spanish scholars of the period."--BOOK JACKET.